Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.plasmid.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and typing of IncC plasmids contributing to antibiotic resistance in Gram-negative bacteria

Abstract: The large, broad host range IncC plasmids are important contributors to the spread of key antibiotic resistance genes and over 200 complete sequences of IncC plasmids have been reported. To track the spread of these plasmids accurate typing to identify the closest relatives is needed. However, typing can be complicated by the high variability in resistance gene content and various typing methods that rely on features of the conserved backbone have been developed. Plasmids can be broadly typed into two groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 119 publications
1
71
1
Order By: Relevance
“…Because KPC160111 was an ST11_KL47/OL101 strain related to other KPC-2 K. pneumoniae (3), the acquisition of pOXA48-L111, which brought the second carbapenemase OXA-48 into an already KPC-2 background, was suggested as a likely scenario for the emergence of this K. pneumoniae that carried both bla KPC-2 and bla OXA-48 . Besides the carriage of the KPC-2 and OXA-48 plasmids, KPC160111 harbored a novel IncC plasmid (194,181 bp), which exhibited hybrid type 1 and type 2 IncC backbone features (8), and had 4 mosaic cassettes holding a total of 25 AMR genes (see Fig. S3).…”
mentioning
confidence: 99%
“…Because KPC160111 was an ST11_KL47/OL101 strain related to other KPC-2 K. pneumoniae (3), the acquisition of pOXA48-L111, which brought the second carbapenemase OXA-48 into an already KPC-2 background, was suggested as a likely scenario for the emergence of this K. pneumoniae that carried both bla KPC-2 and bla OXA-48 . Besides the carriage of the KPC-2 and OXA-48 plasmids, KPC160111 harbored a novel IncC plasmid (194,181 bp), which exhibited hybrid type 1 and type 2 IncC backbone features (8), and had 4 mosaic cassettes holding a total of 25 AMR genes (see Fig. S3).…”
mentioning
confidence: 99%
“…Nevertheless, pVb1796 also contains orf1847, a key feature of type 2 IncC plasmids (Figure S1a, Supporting Information). Remarkably, compared to the plasmid sequences available in GenBank,13 pVb1796 is the only plasmid that carries features of both type 1 and 2 IncC plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…At present, we expect that the bla VMB‐1 gene remains rarely detectable in clinical Enterobacteriaceae isolates as it takes time for transmission of this new antimicrobial resistance gene from the environmental strains to common human pathogens. However, association of the bla VMB‐1 gene with IncC group plasmids implies a high risk of dissemination of such resistance gene as IncC group plasmids have been identified in bacterial strains of various species recovered from both the environment and clinical setting,12,31 with over 200 sequences of IncC plasmids having been reported or deposited in the GenBank since the first report of such plasmid in 2007 13. IncC plasmid was first described among multidrug resistant Aeromonas hydrophila causing disease in cultured fish in the 1970s, when it was combined with IncA plasmids into IncA/C group 32.…”
Section: Resultsmentioning
confidence: 99%
“…IncC and IncA plasmids were long suspected to exclude each other's entry, but the genetic determinants responsible for exclusion were unknown (22)(23)(24)(25). Confusion between exclusion and incompatibility has plagued the nomenclature and typing of these plasmids since the late 1980s (26,31). Nevertheless, Ambrose et al (26) recently confirmed that IncA and IncC replicons are compatible and that the apparent incompatibility between these two plasmid groups most likely resulted from entry exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…IncC plasmids have been typed in two main groups, type 1 and type 2, based on differences within the resistance gene clusters or loss of backbone regions adjacent to them (1). Hybrid plasmids that share features of both types have also been described, as well as subtypes 1a and 1b, which differ by the presence or absence of a 14.5-kb diverged segment (31). We found no clear correlation between IncC plasmid type and the variant of the eexC gene that they carry.…”
Section: Discussionmentioning
confidence: 99%